Formulation of physical education and training program based on multidimensional education data mining - Qiang, Sun (Cluster computing, 2019)
A method for formulation of physical education and training program based on balanced split point field programmable gate array is proposed in this Article to improve the effectiveness of physical education and training program formulation. Firstly, the data collected for physical education and training program was screened based on rough set method to obtain important correlated data for assessment of physical education and training program herein, to achieve attribute reduction of assessment data set and to obtain the key attributes mostly correlated to quality assessment of physical education and training program herein; secondly, C4.5 decision tree algorithm was introduced to construct the non-linear mapping of attribute assessment factor and the quality assessment of physical education and training program herein; at mean time, an interval tree algorithm with continuous balanced split point FPGA acceleration is proposed in this Article to improve the efficiency of quality assessment of physical education and training program herein, which has facilitated the assessment process; at last, the advantages of method proposed in accuracy and efficiency in quality assessment of physical education and training program was verified by test and analysis.